Asia-Pacific security US, Australia and Japan and the new security triangle - Tow, William T. (Asian security studies, 2007)
The aim of this book is to explore the implications stemming from the recent upgrading of Australia-Japan-US security interactions and the implications for Asia-Pacific regional security that these represent. While a fully functioning trilateral security alliance binding Australia, Japan and the United States is unlikely to materialise or supplant existing bilateral arrangements, the convergence of the strategic interests of these three states makes it imperative that the full-range of such interests and the policy ramifications flowing from them warrants extensive investigation. The need to do so is particularly compelling given that the 'Trilateral Security Dialogue' is one of several contending recent approaches to reshaping Asia-Pacific regional security architectures and mechanisms for confronting new strategic challenges in a post-Cold War and post-9/11 environment. Key issues to be considered in this volume include the theoretical and empirical context of 'trilateralism'; the evolving history of the Australia-Japan-United States trilateral security relationship; its connection to and impact on the U.S. bilateral alliance network in Asia; how domestic politics in each country relates to regional security politics; Sino-Australian and Sino-Japanese bilateral security ties; arms control, maritime security and the 'economic security nexus'.